NAVIGATING DIGITAL DISRUPTION: CONSUMER BEHAVIOR-DRIVEN INNOVATION FOR SUSTAINABLE BUSINESS - Sari, Lola Fitria; Wijaya, Agustinus Miranda; Widyastuti, Sri; Asengbaramae, Rowiyah (Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of Digital Innovation and Consumer Behavior on Customer Experience and Competitive Advantage in the context of retail product consumers in the Greater Jakarta area. Using a quantitative approach, data were collected from 200 respondents and analyzed using a structural model. The results showed that Digital Innovation has a significant positive effect on Customer Experience (path coefficient = 0.195; T = 2.538; P = 0.006) and Competitive Advantage (path coefficient = 0.140; T = 1.884; P = 0.030). Consumer Behavior also has a significant positive effect on Customer Experience (path coefficient = 0.381; T = 5.717; P = 0.000) and Competitive Advantage (path coefficient = 0.309; T = 4.179; P = 0.000). Customer Experience is proven to be a significant mediator in the relationship between the two on Competitive Advantage. These findings emphasize the importance of digital innovation, understanding consumer behavior, and customer experience in building sustainable competitive advantage. Therefore, the success of digital innovation must be measured by the extent to which a company creates value for stakeholders, including consumers, society, and the environment. Technology-based innovation, implemented ethically and sustainably, is a key foundation in the Marketing 6.0 era amid ongoing digital disruption